IN VIVO EVALUATION OF MISOPROSTOL FLOATING MICROSPHERES - Kondi Vanitha; Mohan Varma; Allure Ramesh (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Prostaglandin (PG) has been reported to be an important protective and acid suppressive factor in the gastric mucosa. The objective of the study was to develop and evaluate a stomach specific drug delivery system for controlled release of Misoprostal a PE analogue for gastric ulcer induced NSAIDs. Floating microspheres were prepared by emulsification-solvent evaporation method using ethyl cellulose as a polymer, carbopol as mucoadhesive polymer. Ulcers were induced by the oral administration of absolute ethanol (5 mL/kg) to 24 h fasted Wistar male rats (n=8), weighing 200 g. Sodium bicarbonate solution, misoprostal solution and drug loaded microspheres were tested. Formulations were administered orally 1h before the administration of ethanol. Prior to the oral administration, rats were anesthetized with ethylic ether. After 2 h of ethanol administration, animals were sacrificed; the stomachs were removed, opened along he greater curvature and examined for lesion measurements. Ulcer indexes (UI) were calculated. The in vivo evaluation showed that ulcer index values were 0.61 ± 0.14 for the sodium bicarbonate solution, 0.58 ±0.18 for the misoprostal and 0.11 ± 0.06 for the misoprostal-loaded microspheres. The KruskalWallis test detected statistical differences (p =0.002) between the ulcer indexes. The multiple analyses (Student-Newman-Keuls) showed that the misoprostal loaded microspheres presented a gastric ulcer index statistically lower than that of the sodium bicarbonate solution (p = 0.001) and the misoprostal solution (p = 0.021). The percentages of ulceration inhibition were 31 and 75% after the administration of misoprostal solution and microspheres, respectively. In conclusion, the in vivo evaluation showed that the microspheres presented ulcer index lower than the solutions, showing that misoprostal-loaded microspheres were efficient in protecting the stomach against ulcer formation.Key words: Misoprostal, microspheres, ulcer index,